Pengaruh strategi komunikasi humas kantor perwakilan Bank Indonesia - vransisca kissya (Jurnal Syntax Transformation, 2020)
The study was conducted at the Bank Indonesia Branch Office of Maluku in Ambon, with descriptive qualitative research methodology, which made the informants as key informants, key informants and additional informants, with three indicators including: (A). Mission of Bank Indonesia branch of Maluku branch (B). Development of company profile of Bank Indonesia Office of Maluku branch (C). Assessment of the external environment of the Maluku branch office of Bank Indonesia (D). Review and evaluation of matters achieved by the Maluku branch office of Bank Indonesia in each short-term period as a process for control and input for future decision-making.